The role of leaders’ emotions - Lazányi, Kornélia (Applied Studies in Agribusiness and Commerce, 2009)
Western cultures support the notion that the ideal ‘professional’behaviour for a leader is primarily rational and carefully controlled emotionally. The relationship of reason and emotion is often played out as one of mutual exclusion, and moreover as one representing hierarchy of leaders and followers. Power positions in most organizations are ritually emphasized through strict emotional control/suppression. Thus this display of unemotional rationality is held to be synonymous with control, may actually belie emotional and psychical insanities, and indicate organizational incongruities. Since, emotions play crucial role in the regulation of workplace relations. Negative emotions are the basis of awareness and positive ones are that of trust, and hence they both are needed in everyday situations. Leaders’emotions can be used as tools to motivate and to express individualist attention and caring. However, this use of emotions as tools may come at a price for those leaders who are less apt at emotion regulation. In sum, workplace is an emotional place and it is of best interest of the organizational members, – both the leaders and those led, – to understand the leaders’genuine and displayed emotions, their antecedents and their consequences.